A single high-dose irradiation changes accumulation of methotrexate and gene expression levels of SLC and ABC transporters in cancer cells - Sato, Kakeru; Seki, Tatsuya; Mizutani, Asuka; Muranaka, Yuka; Hirota, Shiho; Nishi, Kodai; Yamazaki, Kana; Nishii, Ryuichi; Nakanishi, Takeo; Tamai, Ikumi; Kawai, Keiichi; Kobayashi, Masato (Frontiers in Pharmacology, 2023)
Chemoradiotherapy is frequently used to treat cancer. stereotactic body radiotherapy (SBRT) is a single high-dose radiotherapy used to treat a variety of cancers. Methotrexate (MTX), an anticancer drug, shows affinity for solute carrier (SLC) and ATP-binding cassette (ABC) transporters. This study investigated relationships between accumulation of MTX and gene expression levels of SLC and ABC transporters in cancer cells after a single and high-dose X-ray irradiation. Cancer cell lines were selected from lung and cervical cancer cell line that are commonly used for SBRT and effective with MTX. We examined expression levels of organic anion-transporting polypeptide (OATP)1B1, OATP1B3, OATP1B7, and organic anion transporter (OAT)1 as SLC transporters and multidrug resistance-associated protein (MRP)1 and MRP2 as ABC transporters, using real-time polymerase chain reaction and accumulation of 3H-MTX in cancer cells after 10-Gy irradiation, assuming SBRT. Cells were divided into three groups: control without irradiation; 4 hours after irradiation; and 24 hours after irradiation. In control, gene expression levels of OAT1 in all cells was below the limit of measurement. After irradiation, gene expression levels of OATP1B1/1B3/1B7 showed changes in each cell line. Gene expression levels of MRP1/2 tended to increase after irradiation. Gene expression levels of OATP1B1/1B3/1B7 were much lower than those of MRP1/2. Accumulation of 3H-MTX tended to decrease over time after irradiation. Irradiation of cancer cells thus alters gene expression levels of both SLC transporters (OATP1B1/1B3/1B7) and ABC transporters (MRP1/2) and decreases accumulation of 3H-MTX in cancer cells over time due to elevated expression of MRP1/2.